Prumo: um método para modelagem de elementos de comportamento humano em processos de negócio baseado na teoria da atividade e em propiciações - Augusto Campos Farnese (2014)
In the present work we propose an extension to the traditional BPM (Business Process Modeling) approaches by using techniques and concepts from Usability Engineering. This work aims to enrich the process model with contextual information about human, cultural and environmental aspects. BPM has being widely used to promote organizational improvements and to serve as a basis for software development projects. Although it can describe process functional aspects, traditional BPM methodologies do not pay enough attention to contextual aspects. Knowledge about the context can be very important in conducting a business and for software requirement elicitation. In order to help gathering relevant information about business process context, this work proposes a method called PRUMO, that uses AT (Activity Theory) with the concept of affordances to analyze the process by the users point of view. AT is used to structure and analyze the interaction between the elements that compose the Activities. The Affordances are identified, so we can analyze how an individual interprets the variety of available resources and understand the Activity execution context. PRUMO is evaluated by applying it over PrATIco resulted from an academic work from Cardoso [2006]. The evaluation concludes that by using PRUMO it is easier to gather relevant information about the processo context, which can lead us to a better understanding of the Activity itself and the users needs.